The North Anatolian Fault: an example to regularity of ‘irregular’ seismic behaviour of continental strike-slip faults - Zabcı, Cengiz; Altunel, Erhan; Akyüz, H. Serdar (Copernicus GmbH, 2023)
In the complex puzzling of the lithospheric plates, the transform boundaries and related strike-slip faults are under focus of earth scientists for more than a hundred years not only for their important role in the lithospheric-scale deformation, but also for being sources of destructive earthquakes. Particularly, spatial and temporal seismic behaviour of these faults has been a subject of great curiosity for several decades with a special emphasis on the relationship between their geometry and earthquake recurrence. The North Anatolian Shear Zone (NASZ) is one of these tectonic structures, which makes the northern boundary of the Anatolian Scholle connecting the Hellenic Subduction in the west and the Arabia-Eurasia Collision in the east. This dextral system has a remarkable seismic history, especially in the 20th century, when the westward migrating earthquake sequence generated surface ruptures of about 1100 km with addition of ~140 km from two out of sequence events, 1912 Mürefte and 1949 Elmalı earthquakes, leaving unbroken only Marmara in the west and Yedisu in the east along its most prominent structure, the North Anatolian Fault (NAF).In this study, we aim to review palaeoseismic studies of more than three decades that provide invaluable information on the earthquake history all along the NAF with an attempt to understand which fault pieces have been involved in any of these palaeoevents. Thus, we decided to use their geometric properties, with an assumption that certain geometric discontinuities play an important role as end-points of an earthquake rupture. Palaeoseismological studies are grouped together according to the NAF’s geometric segments, on which they are located. In this classification, we excluded the ones with incomplete dating records or providing indirect evidence (i.e., cores). Then, we used a Bayesian approach to calculate the probability distributions of each palaeoevent, but applied it not to the individual sites but to the tectonostratigraphic data of merged trenches along the same fault segments. Our analyses suggest an ‘irregular’ seismic behaviour of the NAF although there are still gaps in data especially for the central parts. Large geometric complexities (e.g., Niksar step-over, Çınarcık Basin) significantly control the heterogenous stress conditions, but the ‘irregular’ behaviour is not only restricted to the segments close to these structures, but observed almost along the entire fault. In spite of the compiled 118 trench sites with more than 275 trenches, there is still necessity of further studies in order to increase the spatial and temporal resolution of palaeoseismic data along the NAF, especially for its central segments.